Empowering libraries: Strategies for the Future/H. K. Kaul. – New Delhi: DELNET, 2017 (ISBN: 978-93-82735-10-6) - Raghavan, K. S. (Journal of Information and Knowledge, 2017)
Professional library and information science literature in India has been steadily growing. Dr. Kaul’s book entitled ‘Empowering libraries’ is probably the most recent addition to this. Given Dr. Kaul’s rich and long experience as head of the library at the India International Centre which caters to the information needs of some of the most serious researchers in the social sciences and as founder director of DELNET, the most successful library network in India, which continues to grow, the volume should be a welcome addition to the Indian literature that stems from years of experience in institution building and working with serious researchers. The book includes, as stated in the preface, revised versions of Dr. Kaul’s presentations at NACLIN and papers in professional periodicals. The chapters have been grouped under five broad headings; viz., Knowledge and Society, Technology Applications in Libraries, Networking libraries, LIS professionals and Future of Libraries. The headings do reflect contemporary issues confronting librarianship and information service. Given that libraries are facing major challenges and that questions are being raised regarding the continued relevance of libraries in the emerging context, it is very important for members of the profession to re-examine the nature of library / information work and service and to re-fashion and re-position libraries to adapt to the breathtaking changes that are taking place in the information environment. The essays in the book seek to examine the changing role of libraries and LIS professionals in the context of changes that are taking place as a result of developments in information technology.